Third molar impaction and agenesis: influence on anterior crowding - Temitope Esan; Lynne A. Schepartz (Taylor & Francis Group, 2017)
Background Third molar influence on anterior crowding is controversial, but they are assumed to play a major role in compromising dental arch space. Aim To evaluate the relationship among impaction, agenesis and crowding in black South African males. Subjects and method Mandibles and maxillae of 535 black South African males in the Raymond A. Dart Collection of Human Skeletons, University of the Witwatersrand were examined for anterior crowding and third molar agenesis and impaction. Dental crowding was determined using Little's irregularity index. Results Individuals with impaction showed more moderate-to-extreme crowding than those with agenesis. Bilateral third molar presence was more frequently associated with ideal-to-minimal crowding. Weak positive but significant correlations between crowding and impaction were found (mandible, ρ = 0.154, p = 0.000; maxilla ρ = 0.130, p = 0.000). The direction was the opposite for bilateral presence of molars (mandible, ρ = −0.135, p = 0.02; maxilla, ρ = −0.111, p = 0.010). Odds of mandibular crowding were greatest in individuals with impaction (OR = 3.22, CI = 1.716-6.05, p < 0.001). Maxillary results were similar. Conclusion Third molar impaction plays a role in anterior crowding. Third molar presence was not associated with anterior crowding, while agenesis did not explain absence of crowding.